2021
DOI: 10.1016/j.ihj.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The height as an independent risk factor of atrial fibrillation: A review

Abstract: Atrial fibrillation (AF) is characterized by abnormal heart rhythm. Among other well-known associations, recent studies suggest an association of AF with height. Height is related to 50 diseases spanning different body systems, AF is one of them. Since AF, a heterogeneous disease process, is influenced by structural, neural, electrical, and hemodynamic factors, height alters this process through its contribution to increasing atrial and ventricular size, leading to altered conduction patterns, autonomic dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Our observation that an increasing body height, to the contrary, has a positive association with AF also has been noted in previous studies in other populations [ 20 22 ]. In a large Korean cohort study, data from the Korean National Health Insurance Service-National Sample Cohort (NHIS-NSC) from 2002 to 2015 of more than 300,000 individuals who underwent a medical examination between 2006 and 2009 were analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation that an increasing body height, to the contrary, has a positive association with AF also has been noted in previous studies in other populations [ 20 22 ]. In a large Korean cohort study, data from the Korean National Health Insurance Service-National Sample Cohort (NHIS-NSC) from 2002 to 2015 of more than 300,000 individuals who underwent a medical examination between 2006 and 2009 were analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…And in the Danish Diet, Cancer, and Health Study [ 55 ], BMI was found to be significantly associated with AF after adjusting for height, smoking, alcohol consumption, hypertension, diabetes, heart diseases, etc. Similarly, height is also a well-known independent risk factor for AF (as shown by Height → AF) after adjusting for many traditional risk factors as evidenced by many studies [ 56 58 ]. Overall, some of our findings here have lent strong support for some existing causal hypotheses drawn from previous observational cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, standing height was ranked as the fourth most significant feature in our best performing model for AF prediction. Greater height has been identified as a risk factor for AF in several studies [2, 9, 62-64] and in both males [10, 65] and females [65, 66]. Some studies report that taller people have greater heart chamber size [9, 10, 63, 65, 66], meaning a larger left atrial size, which may be potential explanation albeit not a very robust one as AF is driven by left atrial stretch and fibrosis.…”
Section: Discussionmentioning
confidence: 99%